TRADITIONS AND VALUES OF THE UZBEK FAMILY: A PHILOSOPHICAL UNDERSTANDING OF THE ROLE OF THE FAMILY IN MODERN SOCIETY (Uzbekistan Open Conference, 2025)
The article is devoted to the philosophical understanding of the role of the family in modern society. Man by nature appreciates that which is priceless. Making a conclusion from this, the author tries to substantiate the invaluable role of the family in the spiritual moral and material prosperity of society, nation and state. In the article, relying on the knowledge of wise ancestors, philosophically interpreting, a deep and reasonable conclusion is made.